PENYULUHAN DAN PEMBERIAN MATERI DAN DEMO / PRAKTEK PELATIHAN SALON KECANTIKAN KHUSUS MAKE UP WAJAH SEDERHANA DENGAN KONSENTRASI PADA PENGELOLAAN SUMBER DAYA MANUSIA - Whina Ratnawati; Angga Pratama; Anisa Nurdina; Rio Setiawan; Wahadi Siamto (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2021)
Implementation of Community Service is one of the applications of the Tri Dharma of Higher Education which in its implementation makes a positive contribution tosociety. The implementation of this PKM takes the title “Penyuluhan dan pemberian materi dan demo / praktek pelatihan salon kecantikan khusus make up sederhana dengan konsentrasi pada pengelolaan Sumber Daya Manusia“. The location chosen was an orphanage located in the Ciater Serpong area, South Tangeerang City. Where this location has small businesses that still require better human resource management. The method used in the implementation of this PKM is a workshop or training. Where previously the direct observation stage was carried out to find out the problem. That appears at the research location. This training is used to provide an in-depth understanding of human resource management, especially human resource management in small businesses that have been initiated, it is intended that the Orphanage Al-Amien, who consists of caregivers and children, can understand and implement human resource management quite well. In addition to the training on human resource management, on this occasion an explanation was also given about the basics of entrepreneurship and Her specialty salon business is simple makeup. The results of Community Service went very smoothly and all participants who attended were sure to get a pretty good understanding of the material. On At the end of the training session the participants were also given simple practices to support the ability to implement human resource management in small businesses that are already running at the Al-Amien Ciater Orphanage. As a refinement and ensure the ability of participants In applying the material optimally, there will be periodic evaluation stages from a team of lecturers and PKM teaching practitioners.